2017
DOI: 10.2174/1381612823666170525153605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Supplementation on Plasma C-reactive Protein Concentrations: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Results of the present meta-analysis indicated that magnesium supplementation reduces CRP levels among individuals with inflammation (CRP levels > 3 mg/dL). This finding suggests that magnesium supplements may have a beneficial role as an adjuvant for the management of low-grade chronic systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 0 publications
6
41
0
1
Order By: Relevance
“…The finding that low serum magnesium is associated with several adverse CVD risk factors is supported by randomised control trials. Systematic reviews of magnesium supplementation trials provide evidence as to the benefits of magnesium supplementation in reducing metabolic CVD risk factors including blood pressure and glucose as well as CRP levels [ 39 41 ]. Two recent trials have shown magnesium supplementation to improve vascular function [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that low serum magnesium is associated with several adverse CVD risk factors is supported by randomised control trials. Systematic reviews of magnesium supplementation trials provide evidence as to the benefits of magnesium supplementation in reducing metabolic CVD risk factors including blood pressure and glucose as well as CRP levels [ 39 41 ]. Two recent trials have shown magnesium supplementation to improve vascular function [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“… 39 A recent systematic review and meta-analysis of randomized controlled trials support the suggestion that magnesium supplementation will affect markers of inflammatory stress only when they are elevated. 40 In the overall meta-analysis, magnesium treatment did not significantly affect CRP. However, when the analysis was stratified to compare subgroups of studies in populations with baseline plasma/serum CRP concentrations of ≤3 mg/L and >3 mg/L, magnesium treatment significantly decreased CRP in the latter group.…”
Section: Introductionmentioning
confidence: 87%
“…However, when the analysis was stratified to compare subgroups of studies in populations with baseline plasma/serum CRP concentrations of ≤3 mg/L and >3 mg/L, magnesium treatment significantly decreased CRP in the latter group. 40 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is no surprise to find recommendations of increasing the consumption of magnesium to improve health. The scientific evidence backing up that recommendation is based on various randomized clinical trials in which magnesium supplements have been shown to improve several of the parameters analyzed, including plasma lipids, glycemic control, blood pressure, metabolic syndrome, inflammatory markers and endothelial function [27][28][29][30][31][32][33], among others. However, there are also other intervention studies that have detected no such improvements [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%